Informe de resultados del estudio de opinión sociopolítica : abril 2020 - Alfaro Redondo, Ronald; Guzmán Castillo, Jesús 1989-; Cascante Matamoros, María José 1983-; Brenes Peralta, Carlos; Sáenz Bonilla, Juan Pablo 1989-; Camacho Sánchez, Sharon Mariela 1995-; Chinchilla, Vianca (Centro de Investigacion y Estudios Politicos, 2020)
Este informe publicado el 29 de abril de 2020